Moving from an Exception to a Rule: Analyzing Mechanisms in Emergence-Based Institutionalization - Colyvas, Jeannette A.; Maroulis, Spiro (Organization Science, 2015)
We analyze the conditions under which a practice moves from rare and unacceptable to preponderant and legitimate through bottom-up, relational processes. To better understand the mechanisms and contingencies of such “emergence-based institutionalization,” we combine computational agent-based modeling with insights from a setting where a seemingly deviant local practice became institutionalized: the case of the emergence of proprietary disclosure in the academic life sciences. Our approach results in both theoretical and methodological contributions. From a theoretical perspective, we develop propositions related to microlevel processes that lead to the institutionalization of new rules or those that leave existing arrangements unchanged. Our analysis suggests that traditional social explanations, such as organizational reproduction and copying successful peers, are less likely to drive emergence-based institutionalization than cognitive factors that direct individuals to anticipate and preempt the actions of others. From a methodological perspective, we provide an example of how case analysis and computational modeling can be combined to study the varying and contingent roles that normative, social, and cognitive factors play in persistence and change in institutionalization.